2020
DOI: 10.3389/fchem.2020.00250
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling on Aquaporin-3 as Skin Cancer Target: A Virtual Screening Study

Abstract: Aquaporin-3 (AQP3) is one of the aquaglyceroporins, which is expressed in the basolateral layer of the skin membrane. Studies have reported that human skin squamous cell carcinoma overexpresses AQP3 and inhibition of its function may alleviate skin tumorigenesis. In the present study, we have applied a virtual screening method that encompasses filters for physicochemical properties and molecular docking to select potential hit compounds that bind to the Aquaporin-3 protein. Based on molecular docking results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Then, 1000 ps simulations were performed in NVT and NPT ensembles at temperature 300 K. To control the temperature and pressure during the simulation, the Berendsen thermostats and barostats were applied. Both the relaxed systems were subjected to a final MD run for 100 ns with a time step of 2 fs [ 47 ]. For analysis purposes, RMSD, RMSF, R g , SASA, and hydrogen bonding were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 1000 ps simulations were performed in NVT and NPT ensembles at temperature 300 K. To control the temperature and pressure during the simulation, the Berendsen thermostats and barostats were applied. Both the relaxed systems were subjected to a final MD run for 100 ns with a time step of 2 fs [ 47 ]. For analysis purposes, RMSD, RMSF, R g , SASA, and hydrogen bonding were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Protein-ligand docking studies have been used as a virtual screening method of potential AQP modulators, being able to predict their binding modes to the protein ( Martins et al, 2012 ; Madeira et al, 2014b ; Yadav et al, 2020 ). Additionally, molecular docking can be combined with molecular dynamics to confirm the proposed inhibitor binding sites, that can also be characterized through density functional theory calculations ( Muller et al, 2008 ; Martins et al, 2012 ; Verkman et al, 2014 ; de Almeida et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, several approaches have been probed including gold(III) compound complexes [43], mercury compounds [44], as well as selective and potent isoform-specific aquaglyceroporin inhibitors [45]. A very recent study has applied a virtual screening method -molecular docking-to select potential compounds that bind to the AQP3, that is overexpressed in human skin squamous cell carcinoma, to be evaluated for the development of inhibitors to alleviate skin tumorigenesis [46]. It has been shown that dexamethasone and ambroxol can stimulate the mRNA and protein expression of AQP3 and AQP5 in a human airway epithelial cell line (A549 cells) which may imply the potential roles of these AQPs in the regulation of airway hypersecretion, as a target for treating related diseases [47].…”
Section: Aqps As Treatment Strategies and Drug Targetsmentioning
confidence: 99%